PENGARUH PEMBERIAN INFORMASI OBAT TERHADAP TINGKAT PENGETAHUAN DAN KEPATUHAN PASIEN HIPERTENSI DI WILAYAH KOTA JAKARTA PUSAT - Silmi Syauqia Zulfa; Primayanti Nurul Ilmi; Nurfitri Bustamam; Dhigna Luthfiyani Citra Pradana (Jurnal Riset Kefarmasian Indonesia, 2025)
As many as 59.8% of hypertension patients in Indonesia do not regularly take medication since the patient feels healthy. This study aims to analyze the effect of providing drug information on the level of knowledge and adherence to taking medication in hypertensive patients. The study design was a quasi-experimental pre-test and post-test with medication reminders and education for 14 days. The questionnaires used were the Hypertension Knowledge-Level Scale (HK-LS) for knowledge level, and the Morisky Medication Adherence Scale 8 (MMAS-8) for compliance level. A total of 45 people became research respondents. Based on data analysis, data on the characteristics of elderly patients was obtained, totaling 36 people (80%), 30 people (66.7%) were female, based on educational status in the high school category, the maximum was 66.7%, 53.3% actively works, based on the antihypertensive drug used is amlodipine 10 mg as much as 64.5%. The results of the statistical test using the Wilcoxon test were that providing drug information on the level of knowledge hypertensive patients had (p < 0.05), and there was a significant effect between providing drug information on the level of medication adherence for hypertensive patients (p < 0.05). Based on the study, it was concluded that providing reminders and education can significantly increase medication adherence